ГЕНДЕРНА ОСВІТА У СИСТЕМІ ГУМАНІТАРНИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2004)
The article is devoted to the task of providing of gender education in the professional training of students. The author gives his program the genders’ course of theory literature.